Muhadharah Based Speech Competition as a Performance-Based Strategy for Developing Arabic Speaking Skills - Fairuz Subakir; Agus Yasin; Ahmad Ario Sofian; Siti Nikmatul Rochma; Nuraeni Rahmawati (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study examines the role of Muhadharah-based speech competition as a performance-based learning model in enhancing Arabic speaking skills at PMDG Putri 3. Employing a qualitative case study design, this research explores how structured speech activities contribute to students' linguistic competence, communicative confidence, and the development of a language-rich environment. Data were collected through non-participant observation, semi-structured interviews, and document analysis involving students, language supervisors, and teachers. The findings reveal that the competition significantly improves vocabulary acquisition, sentence structure, and pronunciation accuracy through systematic preparation and repeated performance. Furthermore, the program fosters students' confidence and motivation by providing authentic communicative experiences in a competitive yet collaborative setting. The study also demonstrates that speech competition plays a crucial role in sustaining a dynamic language environment, where Arabic is actively practiced beyond formal instruction. Theoretically, this research positions Muhadharah-based speech competition as a hybrid model integrating performance-based learning and CLIL oriented approaches while incorporating rhetorical competence and authentic assessment. This study contributes to Arabic language pedagogy by reconceptualizing speech competition as a structured instructional strategy rather than a supplementary activity. It is recommended that language institutions adopt performance oriented programs to enhance communicative competence in meaningful and sustainable ways.